Three keys : a novel - Pritchett, Laura, 1971- (Dell, 2024)
"Becoming invisible is painful . . . unless you know how to work it. Ammalie Dean has just lost the three keys of her life's purpose - her husband, her job, and her role as a mom after her son went off to college. She's also mystified to find herself in middle age - how exactly had that happened? The idea of becoming irrelevant, invisible, of letting her life vaguely slip away-well, the terror of that has her driving through Nebraska with a fork in her hair. What she does have is this: three literal keys, saved in a drawer for years. Keys to homes she hopes will be empty, from her and her husband's past - homes she plans on breaking into. And so Ammalie embarks on an international and increasingly complicated journey - criminal behavior turns out to be challenging - as she seeks to find a life truly her own. And that middle age business? As someone breaking the law, she finds there's real benefit to being invisible while she works on becoming the striking, bold, and very much manifested self she wants to be. Laura Pritchett, winner of the PEN USA Award for Fiction and the Colorado Book Award, offers a delightful exploration of the very serious business of living a full and honest life. Filled with love, heartbreak, and criminal behavior, Three Keys tackles the unavoidable sorrows and joys coming of age (again) with the zest and vigor that it deserves"--